Weight bearing training alleviates muscle atrophy and pyroptosis of middle-aged rats - Fu, Pengyu; Gong, Lijing; Yang, Luyao; Tang, Shuning; Ma, Fangyuan (Frontiers in Endocrinology, 2023)
Background: Age-related muscle atrophy and adipose accumulation begin to occur since young and middle-age, and exercise in early age has a positive effect on improving body composition. As a cell death process, pyroptosis may be play an essential role in age-related low-grade inflammation. This study aims to explore the alleviation of muscle atrophy by weight-bearing training with an increase in age via inhibiting pyroptosis. Methods: ninety 8-month-old male SD rats were randomly divided into 3 groups: (1) normal baseline group (N group, n=10), sacrificed after adaptive feeding; control group (C group, n=40) and weight-bearing running group (R group, n=40). The blood sample, adipose tissue (AT) and extensor digitorum longus (EDL) were collected after 8-, 16-, 24- and 32-weeks intervention. Results: The body weight, muscle mass, fat mass, plasma lipid, AT wet weight and adipocyte cross-sectional area (CSA), apoptosis rates of AT and EDL were increased, while the muscle mass, wet weight and fiber CSA of EDL were decreased by aging, which were reversed by exercise; weight-bearing training promotes protein synthesis in EDL, inhibits protein degradation in EDL and expression of pyroptotic key proteins in EDL and AT in rats. Conclusions: Weight-bearing training improves the body composition and alleviates age-related muscle atrophy of rats, and its mechanism may be related to the inhibition of pyroptosis in EDL and AT and the improvement of muscle protein metabolism.